The Civil War : the first year told by those who lived it - Simpson, Brooks D.; Sears, Stephen W.; Sheehan-Dean, Aaron Charles (New York : Library of America : Distributed to the trade in the U.S. by Penguin Group, 2011)
Collects diaries, letters, and eyewitness accounts of individuals from all walks of life on such topics as Lincoln's election, the firing on Fort Sumter, and the battle at Shiloh.
Maps on lining papers.
Includes bibliographical references (p. 744-792) and index.
Keywords: United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Personal narratives; United States -- History -- Civil War, 1861-1865 -- Sources